Early Detection of Contamination Vibrio parahaemolyticus and Escherichia coli in Fisheries Product Using Multiplex Polymerase Chain Reaction - Nur Hasanah; Putu Eka Sudaryatma; Imanuddin Razaq; Ni Nyoman Eriawati; Wahyu Andy Nugraha; Hidayati Kumalasari; Ni Putu Arya Shintya Anggraeni; Ida Ayu Mirah Meliana Dewi (Jurnal Sain Veteriner, 2022)
The fisheries sector provided a significant contribution to the Indonesian economy by increasing export activities in every year. The exported fisheries product are categorized of live fish, frozen fish, preservation products from various types of fish, crustaceans, and molluscs. The contamination of pathogenic bacteria Vibrio parahaemolyticus and Escherichia coli causing healthy problems originating from the fishery sector (sea-food borne disease). These two bacteria contaminated fisheries product is due to mishandling and storaging in the processing, which causes acute diarrhea, gastrointestinal infections and fever. The multiplex polymerase chain reaction (mPCR) method was developed to increase the efficiency of time, effort and accuracy of the bacterial contamination testing process. The mPCR method begins with the optimization of the two bacterial gene targets, sensitivity test, specificity test and then applied to samples of fishery products. The mPCR method is carried out in two mechanisms, namely “one-run” conducted from bacterial colonies isolated on agar media and “one-tube” which is applied directly from fishery products. The results of the development of the mPCR method on V. parahaemolyticus and E. coli resulted in sensitivity at concentrations of DNA 5.6 pg/ml and DNA 5.5 pg/ml, respectively. One-tube mPCR application obtained 7 positive colonies of V. parahaemolyticus and 38 positive colonies of E. coli. Meanwhile, one-tube mPCR which was applied directly from shrimp samples could identify the two bacteria.